The USborne book of Silly Jokes - Hawthorn, Philip (Tulsa, Oklahoma : EDC Publishing, 1991)
Colorful cartoon characters tell jokes, gags, riddles and rhymes about everything from Martians to marzipans; skunks to skeletons.
Keywords: Children book